“Performance” Pembawa Acara yang Profesional - Ermawati Arief (Fakultas Bahasa dan Seni UNP, 2009)
Master of Ceremony (MC) is a person whose responsibellity is to see that formal social occasions are carried out properly. The occasions will only run effectively and interestingly if it is led by a professional MC.some requirements to be fulfilled by an ideal MC are as follow: a)be physically healthy b) have particular knowledge about being MC c) have polite personality d) have nice voice, espexially for MC working in formal occasions. Keywords: master of ceremony, professional, requirement, physic, knowledge, personality, nice